2017
DOI: 10.21873/anticanres.11679
|View full text |Cite
|
Sign up to set email alerts
|

Safety of First-line Chemotherapy with Metronomic Single-agent Oral Vinorelbine in Elderly Patients with NSCLC

Abstract: Metronomic oral vinorelbine is safe in elderly patients, allowing for long-term disease stabilization with optimal patient compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 26 publications
(43 reference statements)
3
11
0
Order By: Relevance
“…Vinorelbine is as an oral formulation and that is convenient to be taken. Previous studies have shown that metronomic oral vinorelbine alone can be safely used in elderly patients with advanced NSCLC [ 4 , 5 ]. But in the present study, we investigated the impact of MET NVB and/or Endostar on the frequency of CEPs, expression of CD31, VEGF, and HIF-1α in tumor-bearing mice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Vinorelbine is as an oral formulation and that is convenient to be taken. Previous studies have shown that metronomic oral vinorelbine alone can be safely used in elderly patients with advanced NSCLC [ 4 , 5 ]. But in the present study, we investigated the impact of MET NVB and/or Endostar on the frequency of CEPs, expression of CD31, VEGF, and HIF-1α in tumor-bearing mice.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor growth and metastasis by antagonizing angiogenesis are also inhibited [ 3 ]. Previous studies have shown that metronomic oral Vinorelbine can be safely used in elderly patients with advanced NSCLC, allowing for long-term disease stabilization combined with optimal patient compliance [ 4 , 5 ]. Together, these studies, including numerous preclinical and clinical trials, provide accumulative evidence that MET maintains the therapeutic response, minimizes relapse after conventional chemotherapy, and overcomes resistance [ 1 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Platinum-based chemotherapy is most commonly used in patients with advanced or recurrent NSCLC and ED-SCLC (Extensive Disease Small Cell Lung Cancer) 3 , 6 , 7 . However, the long-term benefit of first-line chemotherapy is limited, and some studies showed that median overall survival was only 8 months in patients with advanced NSCLC patients, and only 9 months in the patients with ED-SCLC 8 , 9 . In recent years, biological agents, such as bevacizumab and cetuximab, among others, have been added to chemotherapy regimens.…”
Section: Introductionmentioning
confidence: 99%